Teaching About Gender and Work: Using Case Studies for Team Projects - Bach, Rebecca (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The course that I developed, Gender, Work and Organizations, was created to serve as both an elective for the Sociology major and an elective in the interdisciplinary certificate program, Markets and Management Studies. The approach in the M&M certificate program tends to be very applied and practical. And, students are generally encouraged to have real world experience in team projects. With these factors in mind, I developed a case study project. The cases used for the project are drawn from actual court cases or from fictional cases found in either a case studies text (Konrad, Alison, Cases in Gender and Diversity in Organizations; DeLaat, Jacqueline, Gender in the Workplace: A Case Study Approach, etc.) or from one of the online case clearinghouses (e.g. The European Case Clearing House).